Date palm seed extract for mild steel corrosion prevention in HCL medium - Mohammed, Naba Jasim; Norinsan, Kamil Othman; Al Gburi, Ahmed Jamal Abdullah; M. Yusop, Rahimi (MDPI, 2023)
The inhibition effects of the date palm seed extract corrosion of mild steel in 0.5 M HCl at different concentrations are investigated by potentiodynamic polarisation (PDP), electrochemical impedance spectroscopy (EIS) and weight loss tests. Additionally, this study provides a fundamental understanding of aromatic adsorption on iron (Fe) surfaces. Furthermore, the surface morphology and the extracts are performed using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The maximum inhibition efficiency of 95, 96, and 91% were realised at 1400 mg/L for PDP, EIS, and weight loss, respectively. The inhibitive action of the DPS extract against mild steel corrosion in an acid solution has been supported by SEM analysis. The FTIR showed that the extract contained hydroxyl (−OH) and methoxyl (−OCH3) functional groups. The DFT depicted the adsorption sites at the oxygen (O) and carbon (C) atoms as deduced from the Fukui functions, Mulliken atomic charge, and the highest occupied molecular orbital-lowest occupied molecular orbital (HOMO-LUMO) analysis. The DPS preferred to form chemical bonds by donating electrons to the Fe surface. The coordinate bonds between the O and C atoms and the metal surface resulted in a high inhibition efficiency value. In conclusion, date palm seed extract is an effective inhibitor to protect mild steel from corrosion in an acidic medium